Cantilever bending based on humidity-actuated mesoporous silica/silicon bilayers - Ganser, Christian; Fritz-Popovski, Gerhard; Morak, Roland; Sharifi, Parvin; Marmiroli, Benedetta; Sartori, Barbara; Amenitsch, Heinz; Griesser, Thomas; Teichert, Christian; Paris, Oskar (Beilstein Journal of Nanotechnology, 2016)
We use a soft templating approach in combination with evaporation induced self-assembly to prepare mesoporous films containing cylindrical pores with elliptical cross-section on an ordered pore lattice. The film is deposited on silicon-based commercial atomic force microscope (AFM) cantilevers using dip coating. This bilayer cantilever is mounted in a humidity controlled AFM, and its deflection is measured as a function of relative humidity. We also investigate a similar film on bulk silicon substrate using grazing-incidence small-angle X-ray scattering (GISAXS), in order to determine nanostructural parameters of the film as well as the water-sorption-induced deformation of the ordered mesopore lattice. The strain of the mesoporous layer is related to the cantilever deflection using simple bilayer bending theory. We also develop a simple quantitative model for cantilever deflection which only requires cantilever geometry and nanostructural parameters of the porous layer as input parameters.
Keywords: AFM cantilever; bilayer bending; grazing incidence small-angle X-ray scattering (GISAXS); mesoporous film; sorption-induced deformation

(untitled) - Lang, H. P.; Baller, M. K.; Berger, R.; Gerber, C.; Gimzewski, J. K.; Battiston, F. M.; Fornaro, P.; Ramseyer, J. P.; Meyer, E.; Güntherodt, H. J. (Anal. Chim. Acta, 1999)

(untitled) - Lang, H. P.; Ramseyer, J. P.; Grange, W.; Braun, T.; Schmid, D.; Hunziker, P.; Jung, C.; Hegner, M.; Gerber, C. (J. Phys.: Conf. Ser., 2007)

(untitled) - Huber, F.; Lang, H. P.; Backmann, N.; Rimoldi, D.; Gerber, C. (Nat. Nanotechnol., 2013)

(untitled) - Huber, F.; Lang, H. P.; Zhang, J.; Rimoldi, D.; Gerber, C. (Swiss Med. Wkly., 2015)

(untitled) - Dawson, C.; Vincent, J. F. V.; Rocca, A.-M. (Nature, 1997)

(untitled) - Elbaum, R.; Zaltzman, L.; Burgert, I.; Fratzl, P. (Science, 2007)

(untitled) - Harrington, M. J.; Razghandi, K.; Ditsch, F.; Guiducci, L.; Rueggeberg, M.; Dunlop, J. W. C.; Fratzl, P.; Neinhuis, C.; Burgert, I. (Nat. Commun., 2011)

(untitled) - Paris, O.; Burgert, I.; Fratzl, P. (MRS Bull., 2010)

(untitled) - Reyssat, E.; Mahadevan, L. (J. R. Soc., Interface, 2009)

(untitled) - Erb, R. M.; Sander, J. S.; Grisch, R.; Studart, A. R. (Nat. Commun., 2013)

(untitled) - Xue, Y.; Markmann, J.; Duan, H.; Weissmüller, J.; Huber, P. (Nat. Commun., 2014)

(untitled) - Balzer, C.; Morak, R.; Erko, M.; Triatafillidis, C.; Hüsing, N.; Reichenauer, G.; Paris, O. (Z. Phys. Chem., 2015)

(untitled) - Gor, G. Yu.; Neimark, A. V. (Langmuir, 2010)

(untitled) - Brinker, C. J.; Lu, Y.; Sellinger, A.; Fan, H. (Adv. Mater., 1999)

(untitled) - Dourdain, S.; Bardeau, J.-F.; Colas, M.; Smarsly, B.; Mehdi, A.; Ocko, B. M.; Gibaud, A. (Appl. Phys. Lett., 2005)

(untitled) - Yan, M.; Henderson, M. J.; Gibaud, A. (Appl. Phys. Lett., 2007)

(untitled) - Ganser, C.; Hirn, U.; Rohm, S.; Schennach, R.; Teichert, C. (Holzforschung, 2014)

(untitled) - Hutter, J. L.; Bechhoefer, J. (Rev. Sci. Instrum., 1993)

(untitled) - Amenitsch, H.; Rappolt, M.; Kriechbaum, M.; Mio, H.; Laggner, P.; Bernstorff, S. (J. Synchrotron Radiat., 1998)

(untitled) - Sharifi, P.; Marmiroli, B.; Sartori, B.; Cacho-Nerin, F.; Keckes, J.; Amenitsch, H.; Paris, O. (Bioinspired, Biomimetic Nanobiomater., 2014)

(untitled) - Tate, M. P.; Urade, V. N.; Kowalski, J. D.; Wei, T.-c.; Hamilton, B. D.; Eggiman, B. W.; Hillhouse, H. W. (J. Phys. Chem. B, 2006)

(untitled) - Erko, M.; Wallacher, D.; Brandt, A.; Paris, O. (J. Appl. Crystallogr., 2010)

(untitled) - Ciddor, P. E. (Appl. Opt., 1996)

(untitled) - Grosso, D.; Balkenende, A. R.; Albouy, P. A.; Ayral, A.; Amenitsch, H.; Babonneau, F. (Chem. Mater., 2001)

(untitled) - Zhao, D.; Feng, J.; Huo, Q.; Melosh, N.; Fredrickson, G. H.; Chmelka, B. F.; Stucky, G. D. (Science, 1998)

(untitled) - Boissiere, C.; Grosso, D.; Lepoutre, S.; Nicole, L.; Bruneau, A. B.; Sanchez, C. (Langmuir, 2005)

(untitled) - Prass, J.; Müter, D.; Fratzl, P.; Paris, O. (Appl. Phys. Lett., 2009)

(untitled) - Günther, G.; Prass, J.; Paris, O.; Schoen, M. (Phys. Rev. Lett., 2008)

(untitled) - Hopcroft, M. A.; Nix, W. D.; Kenny, T. W. (J. Microelectromech. Syst., 2010)

(untitled) - Scherer, G. W. (J. Am. Ceram. Soc., 1986)

(untitled) - Timoshenko, S. (J. Opt. Soc. Am., 1925)

(untitled) - Fritz-Popovski, G.; Morak, R.; Schöberl, T.; Van Opdenbosch, D.; Zollfrank, C.; Paris, O. (Bioinspired, Biomimetic Nanobiomater., 2014)

(untitled) - Zlotnikov, I.; Shilo, D.; Dauphin, Y.; Blumtritt, H.; Werner, P.; Zolotoyabko, E.; Fratzl, P. (RSC Adv., 2013)

Cellular Solids, Structure and Properties - Gibson, L. J.; Ashby, M. F. (Cambridge University Press, 1999)

(untitled) - Ryoo, R.; Ko, C. H.; Kruk, M.; Antochshuk, V.; Jaroniec, M. (J. Phys. Chem. B, 2000)

(untitled) - Müter, D.; Jähnert, S.; Dunlop, J. W. C.; Findenegg, G. H.; Paris, O. (J. Phys. Chem. C, 2009)

(untitled) - Gor, G. Y.; Bertinetti, L.; Bernstein, N.; Hofmann, T.; Fratzl, P.; Huber, P. (Appl. Phys. Lett., 2015)

(untitled) - Bangham, D. H.; Fakhoury, N. (J. Chem. Soc., 1931)

(untitled) - Gor, G. Yu.; Paris, O.; Prass, J.; Russo, P. A.; Ribeiro Carrott, M. M. L.; Neimark, A. V. (Langmuir, 2013)

(untitled) - Prass, J. (Humboldt-Universität, 2011)

(untitled) - Mogilnikov, K. P.; Baklanov, M. R. (Electrochem. Solid-State Lett., 2002)

(untitled) - Fan, H.; Hartshorn, C.; Buchheit, T.; Tallant, D.; Assink, R.; Simpson, R.; Kissel, D. J.; Lacks, D. J.; Torquato, S.; Brinker, C. J. (Nat. Mater., 2007)

(untitled) - Dourdain, S.; Britton, D. T.; Reichert, H.; Gibaud, A. (Appl. Phys. Lett., 2008)